THE ONTOLOGICAL ASPECTS OF JAIN SOTERIOLOGY: WITH A PARTICULAR REFERENCE TO THE BONDED AND LIBERATED STATES OF THE SOUL - Bevelacqua, Ana Bajzelj (Asian Horizons, 2011)
Ātma which is free from the defect of Karma gets to the highest point of the universe, knows all and perceives all, and obtains the transcendental bliss everlasting. (Kundakunda, Pañcāstikāya-sāra) Jesus says, ‘If your leaders say to you, “Look, the Father’s rule is in the sky,” then the birds of the sky will precede you. If they say to you, “It is in the sea,” then the fish will precede you. Rather the Father’s rule is inside you and outside you. When you know yourself, then you will be known, and you will understand that you are children of the living Father. But if you do not know yourselves, you live in poverty, and you are poverty.’ (Gospel of Thomas)